Concurrent COVID-19 and Acute HIV: A Case Report and Diagnostic Review - Kelly A. Johnson; Sally Graglia; Elizabeth D. Lynch; Joanna De Mesa; Erin Antunez; Sandra Torres; Susa Coffey; Stephanie E. Cohen (Case Reports in Medicine)
A 26-year-old male presented to the emergency department feeling unwell in February of 2021 with symptoms including diaphoresis, loose stools, and loss of taste sensation. Workup not only confirmed a diagnosis of COVID-19 but also revealed discordant HIV test results, with a reactive fourth-generation antigen/antibody test but a negative HIV-1/2 differentiation immunoassay. Subsequent HIV viral load testing obtained two days later ultimately established a diagnosis of acute HIV (AHI). Screening for HIV and other sexually transmitted infections decreased during the COVID-19 pandemic. It is critical that providers (1) continue recommended screening for HIV as an essential service; (2) consider acute HIV in the differential when evaluating patients with acute viral syndromes; (3) recognize that AHI can occur concurrently with other infections, including COVID-19; and (4) understand the differential diagnosis for discordant HIV test results and know when HIV viral load testing is needed to resolve such discordant results.